What is the role of placebo in neurotherapeutics?. (2nd January 2022) - Frisaldi, Elisa; Shaibani, Aziz; Trucco, Marco; Milano, Edoardo; Benedetti, Fabrizio
ABSTRACT: Introduction: The widespread use of the word 'placebo' in the medical literature emphasizes the importance of this phenomenon in modern biomedical sciences. Neuroscientific research over the past thirty years shows that placebo effects are genuine psychobiological events attributable to the overall therapeutic context, and can be robust in both laboratory and clinical settings. Areas covered: Here the authors describe the biological mechanisms and the clinical implications of placebo effects with particular emphasis on neurology and psychiatry, for example in pain, movement disorders, depression. In these conditions, a number of endogenous systems have been identified, such as endogenous opioids, endocannabinoids, and dopamine, which contribute to the placebo-induced benefit. Expert opinion: Every effort should be made to maximize the placebo effect and reduce its evil twin, the nocebo effect, in medical practice. This does not require the administration of a placebo, but rather the enhancement of the effects of pharmacological and nonpharmacological treatments through a good doctor–patient interaction.